A Buddhist Assay on Emotions: The Case of Edgar - Olivia Coulomb (Miranda: Revue Pluridisciplinaire du Monde Anglophone)
This paper argues that the practice and teaching of Asian spirituality is a powerful tool to learn about people as well as oneself. Not only does Buddhism promote a right way of life but it also underpins emotions that beget rightful feelings, actions and reactions. As a matter of fact, in King Lear most characters see their lives completely altered because they let their emotions get the better of them. The reception of their feelings largely paves the way for their irrational emotions. Nonetheless, Edgar stands apart from this pattern. Accepting his fate, his behaviour is one of rational acceptance and stoic wisdom. When others would be mad with rage, he merely concludes with “Edgar, I nothing am” (2.2.171). Neither does he intend desperate actions but only humbles himself: “Whiles I may scape / I will preserve myself, and am bethought / To take the basest and the most poorest shape / That ever penury in contempt of man / Brought near the beast” (2.2.155-9). From this perspective, I would like to argue that Edgar’s reception of emotions is fully part and parcel of his distinctive uniqueness. Indeed, although Shakespeare’s knowledge of Asia and its spirituality was quite imprecise and he probably never set foot in this part of the world (Dobson), the way Edgar receives his hardship without drastic passionate reactions underlines an ongoing learning curve akin to some elements in Asian spirituality.